Chinese renewable energy technology exports: The role of policy, innovation and markets - Jing Cao; Felix Groba (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Chinese companies have become major technology producers, with the largest share of their output exported. This paper examines the development of solar PV and wind energy technology component (WETC) exports from China and the competitive position of the country`s renewable energy industry. We also describe the government's renewable energy policy and its success in renewable electricity generation as well as increasing renewable energy innovation and foreign knowledge accumulation, which may drive export performance. We aim at empirically identifying determinants of Chinese solar PV and WETC exports. We estimate an augmented gravity trade model using maximum likelihood estimation. Besides controlling for standard variables derived from the gravity literature, we consider additional explanatory factors by accounting for market, policy and innovation effects steaming from both importing countries and China. We use a panel dataset representing annual bilateral trade flows of 43 countries from the developed and developing world that imported solar PV and WETCs from China between 1996 and 2008. The analysis shows that while the national market remained small for solar PV, the industry successfully entered foreign markets. The export performance of firms producing WETC increased but remained relatively small while the country developed a large home market. Empirical results indicate that high income countries, with a large renewable energy market and demand side policy support scheme, in terms of incentive tariffs, are increasingly importing solar PV components from China. We show that trade costs have a negative impact on exports of solar PV components but not WETC. Additionally, we find a positive impact of research and development (R&D) appropriation growth, especially from provincial governments in China, but no evidence that bilateral knowledge transfer and indigenous innovation affect exports.
Keywords: C32; F14; O30; Q42; Q48; Q56; 330; China; Gravity model; Trade; Innovation; Policy; Renewable Energy Technologies